2018
DOI: 10.1111/hsc.12618
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity or dissonance? A systematic review of pharmacist and GP views on community pharmacy services in the UK

Abstract: There has been a strong policy emphasis over the past decade on optimising patient-centred care and reducing general practitioners' (GPs') workload by extending community pharmacy services and collaboration between pharmacists and GPs. Our aim was to review current evidence of pharmacists' and GPs' views of extended community pharmacy services and pharmacists' roles in the United Kingdom (UK). A systematic review was undertaken looking at UK studies investigating pharmacists' and/or GPs' views of community pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 108 publications
1
55
0
Order By: Relevance
“…Building a supportive culture for independent prescribing relies upon IPs establishing strong inter‐professional relationships with colleagues (Smith et al, ; Stenner et al, ). However, fostering inter‐professional relationships could be challenging for IPs in primary care settings such as community pharmacy where contact with physicians and other healthcare professionals is often limited (Bradley, Ashcroft, & Crossley, ; Hindi, Jacobs, & Schafheutle, ; Noblet, Marriott, Graham‐Clarke, & Rushton, ). Moreover, IPs could also encounter difficulties accessing patient records, ongoing training and clinical supervision depending on their healthcare settings (Courtenay et al, ; Hindi, Schafheutle, & Jacobs, ; Stenner et al, ; Weeks, George, Maclure, & Stewart, ).…”
Section: Discussionmentioning
confidence: 99%
“…Building a supportive culture for independent prescribing relies upon IPs establishing strong inter‐professional relationships with colleagues (Smith et al, ; Stenner et al, ). However, fostering inter‐professional relationships could be challenging for IPs in primary care settings such as community pharmacy where contact with physicians and other healthcare professionals is often limited (Bradley, Ashcroft, & Crossley, ; Hindi, Jacobs, & Schafheutle, ; Noblet, Marriott, Graham‐Clarke, & Rushton, ). Moreover, IPs could also encounter difficulties accessing patient records, ongoing training and clinical supervision depending on their healthcare settings (Courtenay et al, ; Hindi, Schafheutle, & Jacobs, ; Stenner et al, ; Weeks, George, Maclure, & Stewart, ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings, nevertheless, highlight that GPs and other staff from family practice place high value on the perceived need for communication between general practice and community pharmacy, community pharmacy’s local knowledge of patients and opportunities for direct pharmacist/patient contact. This finding is somewhat surprising in light of research that has identified poor collaboration between GPs and community pharmacists in relation to the implementation of extended services in the UK and the focus by the UK government to improve these collaborations . Possible explanations may be that GP views are not as dominant as community pharmacist views within this literature or that the views of other practice staff who may deal with community pharmacy more regularly are not usually included.…”
Section: Discussionmentioning
confidence: 85%
“…Despite patients overall being broadly positive for pharmacists providing extended services, awareness is low [4,[24][25]. Increased collaboration between GPs and pharmacists has been identified as key to successful implementation and integration of new pharmacy services, with studies reporting these services not always perceived as beneficial or useful from the GPs' point of view [26][27].…”
Section: Discussionmentioning
confidence: 99%